MicroRNA‐203 mimics age‐related aortic smooth muscle dysfunction of cytoskeletal pathways. Issue 1 (9th August 2016) - Nicholson, Christopher J.; Seta, Francesca; Lee, Sophie; Morgan, Kathleen G.
Abstract: Increased aortic stiffness is a biomarker for subsequent adverse cardiovascular events. We have previously reported that vascular smooth muscle Src‐dependent cytoskeletal remodelling, which contributes to aortic plasticity, is impaired with ageing. Here, we use a multi‐scale approach to determine the molecular mechanisms behind defective Src‐dependent signalling in an aged C57BL/6 male mouse model. Increased aortic stiffness, as measured in vivo by pulse wave velocity, was found to have a comparable time course to that in humans. Bioinformatic analyses predicted several miRs to regulate Src‐dependent cytoskeletal remodelling. qRT‐PCR was used to determine the relative levels of predicted miRs in aortas and, notably, the expression of miR‐203 increased almost twofold in aged aorta. Increased miR‐203 expression was associated with a decrease in both mRNA and protein expression of Src, caveolin‐1 and paxillin in aged aorta. Probing with phospho‐specific antibodies confirmed that overexpression of miR‐203 significantly attenuated Src and extracellular signal regulated kinase (ERK) signalling, which we have previously found to regulate vascular smooth muscle stiffness. In addition, transfection of miR‐203 into aortic tissue from young mice increased phenylephrine‐induced aortic stiffness ex vivo, mimicking the aged phenotype. Upstream of miR‐203, we found that DNA methyltransferases (DNMT) 1, 3a, and 3b are also significantly decreased in the aged mouse aorta and that DNMT inhibition significantly increases miR‐203 expression. Thus, the age‐induced increase in miR‐203 may be caused by epigenetic promoter hypomethylation in the aorta. These findings indicate that miR‐203 promotes a re‐programming of Src/ERK signalling pathways in vascular smooth muscle, impairing the regulation of stiffness in aged aorta.